Correlation Between Warfarin Levels in the Blood and the Value of Normal INR in Fibrillation Atrium Inpatients - Suryoputri, Masita Wulandari; Endriastuti, Nialiana Endah; Ilma, Dewi Latifatul; Azzahra, Alfita (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2024)
Background: Warfarin is an anticoagulant inhibitor of vitamin K that is effective in preventing systemic embolization in atrial fibrillation patients. Warfarin has a narrow therapeutic index, so it requires monitoring of rates to prevent the occurrence of toxic effects and to ensure the passage of INR values.Objectives: The study aims to find out the correlation between warfarin levels and normal INR values.Methods: Observational research method with the collection of retrospective data on the medical records of patients treated with atrial fibrillation at Prof. Dr. Margono Soekarjo Hospital, Purwokerto, in January 2019–December 2021. Warfarin levels were calculated pharmacokinetically using the steady-state concentration (Css) and plasma concentration (Cp) formulas. Data analysis is carried out using the Spearman test to determine the correlation between warfarin levels and normal INR values.Results: The number of patients with normal INR values was less than the number of patients with abnormal INR values, namely 21 patients and 48 patients. The Spearman test results show a p-value of 0.31 (p>0.05), showing that the correlation between warfarin levels in the blood and the corresponding INR value is not significant (p> 0.05), and the R value in the Spearman test is 0.122, showing that the direction of the correlation is positive with very weak correlation strength.Conclusion: The correlation between warfarin levels in the blood and the appropriate INR value is not significant (p>0.05), where the R value in the Spearman test shows R=0.122, meaning the direction of the correlation is positive with a very weak correlation strength.